THE EFFECT OF COGON GRASS ROOT ETHANOL EXTRACT ON REPRODUCTIVE ORGAN AND EPIDIDYMAL SPERM QUALITY OF MOUSE WITH DIFFERENT AGES - Sudiman, Jaqueline; Widyastuti, Rini; Lubis, Alkaustariyah; Hartady, Tyagita; Syamsunarno, Mas Rizky Anggun Adipurna; Sumarsono, Sony Heru (Universitas Syiah Kuala, 2020)
This study aims to determine changes related to epididymal sperm parameters in mice given cogon grass root ethanol extract (CGREE). The experiment was carried out by dividing three groups of mice aged 4-week old (early pubertal), 8-week old (adult), and 24-week old (old) as control and treatment groups. The treatment groups were given 115 mg/kg body weight of CGREE for 14 days. The mice were sacrificed on day 15 to asses reproductive organ indexes and quality of the epididymal sperm. Index of epididymis and ductus deferens indices significantly reduced in the 4-week old treatment group compared to control (0.23 vs 0.33; 0.08 vs 0.16, respectively), and vesical seminal significantly reduced in 8- week old treatment group compared to control (0.76 vs 0.68). The epididymal sperm quality significantly decreased in all treatment groups, but the sperm concentration in early pubertal group showed an increase. These results indicate that CGREE can enhance several semen parameters in prepubertal and adult mice but this effect is not apparent in old mice.